Sequence determination and comparison of the exfoliative toxin A and toxin B genes from Staphylococcus aureus. - Lee, C Y (1987)
The DNA encoding the exfoliative toxin A gene (eta) of Staphylococcus aureus was cloned into bacteriophage lambda gt11 and subsequently into plasmid pLI50 on a 1,391-base-pair DNA fragment of the chromosome. Exfoliative toxin A is expressed in the Escherichia coli genetic background, is similar in length to the toxin purified from culture medium, and is biologically active in an animal assay. The nucleotide sequence of the DNA fragment containing the gene was determined. The protein deduced from the nucleotide sequence is a polypeptide of 280 amino acids. The mature protein is 242 amino acids. The DNA sequence of the exfoliative toxin B gene was also determined. Corrections indicate that the amino acid sequence of exfoliative toxin B is in accord with chemical sequence data.